English Translation of Sura Al Mulk: A comparative study (Khairulummah, 2023)
Allah, the Almighty, created each and every creature for a very important reason. Every creation exists primarily to serve the Almighty Allah. The Qur'an contains some of the most beautiful names for Allah Almighty. The Quran mentions the noble name "Rab" of Allah Almighty. It refers to the Lord, the owner, and the master who gives humans all forms of nourishing food. Physical and spiritual nourishment are the two different forms. Both have been blessed by Allah, the Almighty, for those living on this earth. For the spiritual maintenance of people, Allah the Almighty sent Messengers and Prophets with revealed books. Muhammad Sallahu aliahi wasaalam is the last Prophet of Allah with the revealed book Quran. Up to the day of judgment, the Quran serves as a guide for everyone. It comprises all instruction aimed toward advancing humankind. It consists of all teaching for the furtherance of human beings. The Quran contains 114 chapters. Each chapter has certain goals and lessons to teach. Although it is in Arabic, it has been translated into every language. The Quran has many English translations available. However, there is disagreement among most people as to what the verses signify i.e. controversy about the meanings of the verses. The current study compared three English translations of the Qur'an, notably Sura Al Mulk by T.B. Irving, Abdullah Yousef Ali, and Marmaduke Pickthall, in order to identify similarities and discrepancies in the meanings of the verses. Sura Al Mulk is a Makki chapter having 30 verses and mostly consists of evidence on the oneness of Allah Almighty. This study was qualitative by nature and thematic by the method in which discourse analysis framework was employed. A three-dimensional analytical framework was used for describing, interpreting, and explaining the text for finding out relationships and differences. All the verses of Sura Al Mulk were explored comparatively. Similarities and differences based on themes were found. All the themes were put in an organized form and then main themes were drawn based on which it was interpreted and concluded. Despite the words' differences, the translation's meaning was the same.
Keywords: Quran,Sura Al Mulk,English translations,T.B Irving,Abdullah Yousuf Ali,Marmaduke Pickthall.